Piil Pesenggiri in Lampung Community: Between Peace Building or Violence Excuse - Fitra (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Changes in the structure of rural communities and structural violence that occurred by design through government policies, made violences in Lampung society. Traditional Lampung society have institutions that are a reference in their daily lives called piil pesenggiri. In this study, the author wants to see the relation between local institutions and violence in Lampung society. This scientific work is a descriptive analytical qualitative research on structural violence that occurs in a multi-ethnic society with emphasis on primary data through interviews with local communities and policy makers and supporting documents. The results showed that there was a decrease in the effectiveness of the independent institutions in the effort to establish peace which was characterized by the slackening of kinship ties and narrow interpretation of the institution. These conditions trigger an escalation of violence in society.